Efektivitas Sistem Informasi Akuntansi dan Kemampuan Teknis Pengguna pada Kinerja Individual Lembaga Perkreditan Desa - Chintia Dewi, Ni Putu Meydiani; Dewi, Ayu Aryista; Kresnandra, A.A.N.A. (E-Jurnal Akuntansi; Vol 30 No 7 (2020), 2020)
Individual performance greatly influences the success of an organization. Each individual is expected to work optimally so that the company's goals can be achieved to the maximum. There are several factors that can affect individual performance, among which are the effectiveness of accounting information systems and the user's technical ability. This research was conducted to obtain empirical evidence regarding the effect of the effectiveness of accounting information systems and the user's technical ability on individual performance. This research was conducted in 35 LPD in Denpasar City. The sample of this research was 105 respondents with a purposive sampling method. Data collection is done by distributing questionnaires. The analysis technique used is multiple linear regression. Based on the results of this study indicate that the effectiveness of accounting information systems and the user's technical ability has a positive effect on individual performance. Keywords: Accounting Information System Effectiveness; User Technical Capabilities; Individual Performance.